2020
DOI: 10.2478/jccm-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use Is Associated with ICU Delirium in Mechanically Ventilated Children

Abstract: IntroductionPediatric delirium is a significant problem when encounterd in an intensive care unit (ICU). The pathophysiology of pediatric delirium is complex and the etiology is typically multifactorial. Even though various risk factors associated with pediatric delirium in a pediatric ICU have been identified, there is still a paucity of literature associated with the condition, especially in extremely critically ill children, sedated and mechanically ventilated.Aim of the studyTo identify factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 33 publications
1
27
1
Order By: Relevance
“…Twenty-seven (16, 18–22, 35, 38–43, 45–59) were prospective in design, two retrospective (36, 37), and two point prevalence (44, 58). Twenty-seven were single-center studies (16, 18–21, 36–43, 45–57, 59), and four were multicenter studies (22, 35, 44, 58), including two multisite point prevalence studies (44, 58). Twenty-seven took place in a PICU (16, 18–22, 35–43, 45–49, 52–54, 56–59), two in a PCICU (51, 55), one in a mixed PICU and PCICU (50), and one across multiple PCICUs or PICUs (44).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-seven (16, 18–22, 35, 38–43, 45–59) were prospective in design, two retrospective (36, 37), and two point prevalence (44, 58). Twenty-seven were single-center studies (16, 18–21, 36–43, 45–57, 59), and four were multicenter studies (22, 35, 44, 58), including two multisite point prevalence studies (44, 58). Twenty-seven took place in a PICU (16, 18–22, 35–43, 45–49, 52–54, 56–59), two in a PCICU (51, 55), one in a mixed PICU and PCICU (50), and one across multiple PCICUs or PICUs (44).…”
Section: Resultsmentioning
confidence: 99%
“…A pooled PD prevalence of 34% (95% CI, 27–41) was estimated from 17 studies that reported prevalence per patient using CAPD ( Fig. 1 ) (36–38, 41, 43–46, 48, 50, 51, 54–59).…”
Section: Resultsmentioning
confidence: 99%
“…1 Although hospitalization in the PICU increases an individual's risk for delirium, we implemented this scale in a subset of the population at a higher risk of developing delirium. 16 To our knowledge, this is the first study assessing the performance of CAPD in this high-risk population.…”
Section: Discussionmentioning
confidence: 90%
“…26 In critically ill pediatric patients, high sound levels have been correlated with increased need for intermittent sedative boluses, and sedatives have been shown to increase risk of delirium in a dose-dependent fashion. 4,19,27 Furthermore, music therapy has been shown to physiologically reduce stress and anxiety, as well as reduce sedation and delirium severity in mechanically ventilated patients, suggesting an interplay between auditory processing, neuroinflammation, and deliriogenic neurotransmission. [28][29][30] Intermittent loud noises presumptively affect sleep quality and quantity, which we know to be diminished in pediatric critical illness.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, use of such medications has been associated with delirium. 4 27 43 Sleep–wake cycles vary as children grow, and infant sleep cycles are not yet mature. 44 Additionally, children thrive on adherence to routines, particularly in the context of medical care and their mental health.…”
Section: Discussionmentioning
confidence: 99%